Investigation of effect of process parameters on suddenly expanded flows through an axi-symmetric nozzle for different Mach numbers using design of experiments - Quadros, Jaimon Dennis; Khan, Sher Afghan; Antony, A J (IOP Publishing, 2017)
Experiments are conducted to determine base pressure variation through micro-jets from a suddenly expanded axisymmetric passage. Four micro-jets having an orifice diameter of 1mm are situated at 900 interims along the base at 6.5 mm from the geometrical axis of the main jet. The Mach number and L/D ratios were the process parameters employed in the study. The flow stream was extended all of a sudden into an axi-symmetric duct of 4.84 cross-sectional area for all the Mach numbers and L/D ratios respectively. The test Mach numbers used in the study was 2, 2.5 and 3; length-to-diameter ratios selected for the sudden expansion tube were 4, 6 and 8. The jets were operated at an overexpansion level of (Pe/Pa = 0.277). The experiments are conducted as per Taguchi design of experiments. From this investigation, one will be able to identify the enlargement length to diameter ratio resulting in maximum increasing or decreasing base pressure. Mathematical models are also developed for base pressure based on Mach number and L/D ratio with a maximum error of ± 10%.